Impact of tourism on the water quality of a lagoon in the Mantaro Valley - Antesano Chávez, Omar Saúl; Rosas Poma, Melisha Erika; Zavala Figueroa, Nataly Johanna (Journal of the University of Zulia, 2022)
The physicochemical characteristics (TDS, EC, salinity and temperature) of the Ñahuimpuquio Lagoon in the Department of Junín in Peru were evaluated.  Monitoring was carried out in the second semester of 2021: 2 months of the dry period (August and September) and 2 months of the rainy period (October and November), at 5 key points within the lagoon; Point 1: wharf area; point 2: Natural spring "Puquio" that feeds the lagoon; point 3: tourist recreation area and food sale; point 4: mouth area of the lagoon; and point 5: center of the Ñahuimpuquio lagoon. The results show that the total dissolved solids according to the NPDWR standard of the USA, locates the water of the Ñahuimpuquio Lagoon at an acceptable quality level for network supply, and acceptable quality for purified jug water and/or bottled water. The salinity in the lagoon oscillates between 297.2 – 312.2 μS/cm; It is considered within the Digesa parameters (700 – 1200 μS/cm), which indicates that the lagoon has low ion toxicity. The electrical conductivity of the lagoon water shows values between (282 - 303.6 CE), being classified as "Good". Regarding the  temperature, the results show values from (18.52 °C - 24.66 °C). Finally, it was shown that there are significant correlations between tourism in the lagoon and the increase in temperature, electrical conductivity and total dissolved solids; but there is no relationship with salinity in the Ñahuimpuquio - Ahuac lagoon.